Human actinomycetoma caused by Actinomadura mexicana in Sudan: the first report. (31st December 2020) - Siddig, Emmanuel Edwar; Nyuykonge, Bertrand; Ahmed, Mohammed Tayfour; Hassan, Rowa; Saad, Eiman Siddig Ahmed; Mhmoud, Najwa Adam; Bakhiet, Sahar Mubarak; van de Sande, Wendy W J; Fahal, Ahmed Hassan
Abstract: Mycetoma is a localized, chronic, granulomatous disease that can be caused by fungi (eumycetoma) or bacteria (actinomycetoma). Of the 70 different causative agents implicated in mycetoma worldwide, Actinomadura madurae is the only one that causes multiple cases on all continents. Recently, new Actinomadura species were described as causative agents of human mycetoma. One of these new causative agents was Actinomadura mexicana, which was identified in Latin America. Here we demonstrate that this causative agent is not confined to Latin America and that it is also a causative agent of actinomycetoma in Sudan. The disease was managed by antibiotic treatment alone and resulted in complete cure after 6 months of treatment, which is quick when compared with actinomycetoma cases caused by other Actinomadura species.